Formation pathways and sources of size-segregated nitrate aerosols in a megacity identified by dual isotopes. (1st November 2021) - Zhu, Yucheng; Zhou, Shengqian; Li, Haowen; Luo, Li; Wang, Fanghui; Bao, Yang; Chen, Ying
Abstract: Nitrate becomes a vital secondary component in atmospheric aerosols, especially in the urban areas with effective control of sulfur emissions. The elucidation of NO3 − formation pathways and sources would be very helpful for accurately modeling and controlling the particle pollution. In this study, the dual isotopic compositions (δ 15 N and δ 18 O) of size-segregated NO3 − aerosols were measured at an urban site of Shanghai in the winter of 2018 and the late summer of 2019. The formation mechanisms and sources of NO3 − in five size-modes and different seasons were explored by combining analyses of dual isotopes, ion concentrations, air mass back trajectories and the Bayesian isotopic mixing model. Our results showed that the δ 18 O-NO3 − values in summer (62.1 ± 12.8‰) were generally lower than those in winter (80.1 ± 9.9‰) with the lowest values in Aitken (sub–0.1 μm) and condensation modes (0.1–0.56 μm, 48.6 ± 9.8‰). This suggested that NO2  + ∙OH pathway probably played a significant role in the NO3 − formation in summer (56.1 ± 4.8%) especially in Aitken and condensation modes, while N2 O5 heterogeneous and NO3  + RH/RSC (hydrocarbons/reduced sulfur compounds) pathways could be critical in winter (55.0 ± 12.6% and 28.3 ± 15.2%, respectively). The isotopic fractionation may play a critical role in the size distribution of δ 15 N-NO3 − . Based on the formation pathways of NO3 − and calculated fractionation factors ε N, the contribution of major NOx sources to NO3 − aerosols in Shanghai was estimated. It was found that diesel engine exhaust contributed to the highest percentages (39.3% and 32.1%) of NO3 − aerosols followed by gasoline engine exhaust (30.9%) and coal combustion (29.4%) in summer and winter, respectively. The contribution of coal combustion was almost doubled in winter compared to summer whereas soil emission decreased. Our results suggest that the impact of diesel engine exhaust on particle pollution in eastern Chinese megacities should be emphasized. Highlights: Formation pathways of NO3 − varied between different aerosol size-ranges and seasons. NO3  + RH/RSC pathway was more significant in winter than in summer. Mobile sources were the main contributor to NO3 − aerosols in Shanghai. Diesel engine exhaust contributed appreciably to NO3 − aerosols.